POLA MUSIM DI INDONESIA TAHUN 2002 SAMPAI 2016 BERDASARKAN EQUIVALENT WATER HEIGHT (EWH) - Rahayu, Safri Yanti; Anjasmara, Ira Mutiara (Geoid, 2020)
Season is the weather that is clearly visible at certain timescales. Based on its geographical location, the most striking seasonal variation in Indonesia is rainfall. Seasonal changes are also called weather changes that result from surface water interactions such as the water cycle. This shows that weather variations are related to changes in water mass on earth. Water availability can be seen from the Equivalent Water Height (EWH) variations obtained from gravity satellite data Gravity Recovery and Climate Experiment (GRACE) then the used of TRMM (Tropical Rainfall Measuring Mission) satellite data can be used to observe rainfall as well as supporting data for GRACE satellites. From the results of GRACE gravity satellite data processing, the largest EWH value was 27.298 cm in January 2015 and the smallest EWH value of -29.816 cm was in June 2004 on Sumatra Island. During the years 2002 to 2016 Changes in seasonal patterns occurred in 2010 and 2015, each of which was caused by extreme changes in rainfall and by the occurrence of El Nino events.